PENURUNAN STRES KLIENCA MAMAE MELALUI GUIDED IMAGERY RELAXTION DAN FAMILY PSYCHOEDUCATION THERAPHY DI RSUP.RD.M.DJAMIL PADANG - Renidayati, Renidayati (Menara Ilmu, 2019)
An increase in Ca Mamae patients every year. This has an impact on the patient's psychologicalproblems. Stress is one of the psychological reactions that arise when a person is diagnosed withcaesarean cancer. One of the non-pharmacological therapies that can be used to overcome stress isguided imagery.The guided imagery was combined with family psychotherapy education. The studyaimed to determine the reduction in stress in patients with ca. mamae through the implementationof guided imagery and therapy for family psychoeducation therapy. Research design "Quasiexperimental pre-post test without control group" with guided imagery intervention and familypsychoeducation therapy therapy.Research sample of 64 people. The screening stage uses theinstrument Depression Anxiety Stress Scale (DASS). Univariate and bivariate data analysis usingthe Paired sample t-test. The results showed a significant decrease in the average stress conditionbefore and after being given a Guided Imagery Relaxtion intervention and family psychoeducationtherapy.The conclusion is significantly that Guided Imagery Relaxation and familypsychoeducation therapy can reduce stress in patients with cataracts. The recommended results ofthe study need to be applied guided imagery relaxation and family psychoeducation therapy asnursing therapy in treating patients with ca mamae at least once a day for 30 minutes.Keywords: stress, mamae ca, guided imagery relaxation and family psychoeducation therapy